1991
DOI: 10.1016/s0006-3495(91)82182-8
|View full text |Cite
|
Sign up to set email alerts
|

Phases of phosphatidyl ethanolamine monolayers studied by synchrotron x-ray scattering

Abstract: For the first time, phospholid monolayers at the air/water interface have been studied by x-ray diffraction and reflection all along the isotherm from the laterally isotropic fluid (the so-called LE phase) to the ordered phases. The model used to analyze the data, and the accuracy of the parameters deduced, were tested by comparing the results obtained with two lipids having the same head group but different chain lengths. Compression of the fluid phase leads predominantly to a change of thickness of the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
126
2
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(148 citation statements)
references
References 32 publications
17
126
2
1
Order By: Relevance
“…This stretching results in a greater thickness of the hydrocarbon region of the lipid. A similar increase of thickness has been observed for the LE phase of the DMPE lipid with compression of the monolayer, [22] as well as with the incorporation of saturated alkanes into DPPC and DPPE monolayers. [23] Estrela-Lopis et al have reported on a similar significant reduction of the tilt angle in mixed DPPC monolayers, being this tilting decrease attributed to significant changes in the conformation of the head group of the lipids.…”
supporting
confidence: 76%
“…This stretching results in a greater thickness of the hydrocarbon region of the lipid. A similar increase of thickness has been observed for the LE phase of the DMPE lipid with compression of the monolayer, [22] as well as with the incorporation of saturated alkanes into DPPC and DPPE monolayers. [23] Estrela-Lopis et al have reported on a similar significant reduction of the tilt angle in mixed DPPC monolayers, being this tilting decrease attributed to significant changes in the conformation of the head group of the lipids.…”
supporting
confidence: 76%
“…As is described for many isotherms, e.g. for DMPE (see [52]), the kink in the isotherm in the film pressure range of 25-30 mN m −1 is referred to as the transition between a coexistence region and a homogeneous solid phase. We therefore conclude that in dynamic surface elasticity measurements ε P is constant over the full range of the coexistence region of crystalline DPPC domains embedded in fluid monolayer phase.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, the DODAB : DOPE layer contains more water because both the amino and phosphate groups of the DOPE are able to establish bonding with water. When in the expanded phase, monolayers of pure phosphatidylethanolamines (PE) that have the same head group but different lengths of chains and degree of unsaturation were found to have relatively high levels of hydration of 14-19 and 8-10 H 2 O/PE molecule, by X-ray diffraction and reflection [48] and X-ray diffraction [49], respectively. Water vapour uptake studies have shown that a 1 : 1 molar mixture of egg phosphatidylcholine and egg phosphatidylethanolamine has an average hydration of 14 H 2 O molecules compared with just nine H 2 O molecules per lipid in pure phosphatidylethanolamine films [50], which is consistent with the higher hydration value for DODAB : DOPE monolayers compared with the DODAB monolayers shown here.…”
mentioning
confidence: 99%